Fight for life - Anderson, Laurie Halse (Vet volunteers, 2007)
With the help of her veterinarian grandmother and the other volunteers at the Wild at Heart Animal Clinic, eleven-year-old Maggie rescues sick puppies from an illegal puppy mill.